Multidisciplinary management of pregnancy and labour in a patient with glycogen storage disease type 1a. Issue 8 (11th August 2021) - Jones, Alice May; Tower, Clare; Green, Diane; Stepien, Karolina M
Abstract : Glycogen storage disease type 1a (GSD 1a) is a metabolic disorder caused by deficiency of an enzyme required for glycogen breakdown, causing hypoglycaemia and lactic acidosis. Metabolic derangements cause disease manifestations affecting the kidneys, liver and platelet function. Physiological changes in pregnancy worsen fasting intolerance and increase reliance on exogenous glucose to avoid lactic acidosis. Fetal macrosomia and declining respiratory function result in high rates of caesarean sections. We report the multidisciplinary team (MDT) management of a 25-year-old woman with GSD 1a in an unplanned pregnancy. Existing percutaneous endoscopic gastrostomy tube feeding, alongside high-calorie drinks and intravenous dextrose during labour, managed the risks of hypoglycaemia and lactic acidosis. Metabolic parameters were regularly monitored and fortnightly growth scans were assessed for macrosomia. Allopurinol was continued throughout the pregnancy to reduce the risk of hyperuricaemia. MDT management optimised maternal and fetal care throughout pregnancy and labour, resulting in a successful vaginal delivery.